Effectiveness and acceptability of myo-inositol nutritional supplement in the prevention of gestational diabetes (EMmY): a protocol for a randomised, placebo-controlled, double-blind pilot trial. Issue 9 (24th September 2018) - Amaefule, Chiamaka Esther; Drymoussi, Zoe; Dodds, Julie; Sweeney, Lorna; Pizzo, Elena; Daru, Jahnavi; Robson, John; Poston, Lucilla; Khalil, Asma; Myers, Jenny; Harden, Angela; Hitman, Graham A; et al.
Abstract : Introduction: Gestational diabetes increases maternal and offspring complications in pregnancy and cardiovascular complications in the long term. The nutritional supplement myo -inositol may prevent gestational diabetes; however, further evaluation is required, especially in multiethnic high-risk mothers. Our pilot trial on myo -inositol to prevent gestational diabetes will evaluate trial processes, assess acceptability to mothers and obtain preliminary estimates of effect and cost data prior to a large full-scale trial. Methods and analysis: EMmY is a multicentre, placebo-controlled, double-blind, pilot, randomised trial, with qualitative evaluation. We will recruit pregnant women at 12–15 +6 weeks' gestation, with gestational diabetes risk factors, from five maternity units in England between 2018 and 2019. We will randomise 200 women to take either 2 g of myo -inositol powder (intervention) or placebo, twice daily until delivery. We will assess rates of recruitment, randomisation, adherence to intervention and follow-up. Gestational diabetes will be diagnosed at 24–28 weeks as per the National Institute for Health and Care Excellence (NICE) criteria (fasting plasma glucose: ≥5.6 mmol/L and 2-hour plasma glucose: ≥7.8 mmol/L). We will assess the effects of myo -inositol on glycaemic indices at 28 weeks and on other maternal, fetal and neonatal outcomes at postnatal discharge. Qualitative evaluation will explore the acceptability of the trial and the intervention among women and healthcare professionals. Cost data and health-related quality of life measures will be captured. We will summarise feasibility outcomes using standard methods for proportions and other descriptive statistics, and where appropriate, report point estimates of effect sizes (eg, mean differences and relative risks) and associated 95% CIs. Ethics and dissemination: Ethical approval was obtained through the London Queen Square Research Ethics Committee (17/LO/1741). Study findings will be submitted for publication in peer-reviewed journals. Newsletters will be made available to participants, healthcare professionals and members of Katie's Team (a patient and public advisory group) to disseminate. Trial registration number: ISRCTN48872100. Protocol version and date: Version 4.0, 15 January 2018.